2022
DOI: 10.1038/s41467-022-32939-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced TDP-43 mobility loss independent of stress granules

Abstract: TAR DNA binding protein 43 (TDP-43) is closely related to the pathogenesis of amyotrophic lateral sclerosis (ALS) and translocates to stress granules (SGs). The role of SGs as aggregation-promoting “crucibles” for TDP-43, however, is still under debate. We analyzed TDP-43 mobility and localization under different stress and recovery conditions using live cell single-molecule tracking and super-resolution microscopy. Besides reduced mobility within SGs, a stress induced decrease of TDP-43 mobility in the cytopl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
3
15
0
Order By: Relevance
“…A biophysical property that defines the dynamicity and is directly related to the potential pathogenicity of SGs is the mobility of SG proteins within the condensates. Prolonged stress conditions reduce protein mobility within SGs, leading to their transition from a liquid-liquid into a liquid-solid phase that compromises SG elimination during the recovery period ( 16 , 22 ). By fluorescence recovery after photobleaching (FRAP), we found that prolonged exposure of parental cells to arsenite reduced the mobility of GFP-G3BP1 protein with concomitant increase in the half-life of recovery (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A biophysical property that defines the dynamicity and is directly related to the potential pathogenicity of SGs is the mobility of SG proteins within the condensates. Prolonged stress conditions reduce protein mobility within SGs, leading to their transition from a liquid-liquid into a liquid-solid phase that compromises SG elimination during the recovery period ( 16 , 22 ). By fluorescence recovery after photobleaching (FRAP), we found that prolonged exposure of parental cells to arsenite reduced the mobility of GFP-G3BP1 protein with concomitant increase in the half-life of recovery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The generation and persistence of aberrant inclusions due to mutations in several genes encoding for SG proteins is regarded as hallmark in neurodegenerative diseases, such as ALS/FTD ( 14 , 15 , 17 ). However, how alterations in SG dynamics contribute to the formation of the toxic protein inclusions and the impact of aberrant SGs in the onset/progression of ALS/FTD is still unclear ( 22 , 23 ). The definition of pathways and development of approaches that promote the elimination of aberrant SGs would allow to assess their role in pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With that said, the exact relationship between SGs and ALS-FTD disease pathogenesis continues to be hotly debated. Other reports show that the RNAs enriched in SGs prevent aggregation of TDP-43 and that TDP-43 aggregation occurs outside of SGs, disrupting the idea that SGs seed TDP-43 aggregation. Furthermore, in contrast to previous reports that observed transiently expressed TDP-43 ALS variants localizing to SGs, TDP-43 M337V is not found in SGs following heat stress that robustly induces SGs in the mouse central nervous system .…”
Section: Introductionmentioning
confidence: 99%